1994
DOI: 10.1002/ajmg.1320510412
|View full text |Cite
|
Sign up to set email alerts
|

Does IQ decline with age in fragile‐X? A methodological critique

Abstract: The recent claims for a decline in intelligence test performance in males and females with fragile-X (fra(X)) syndrome have implications both clinically and in evaluating the underlying neurological basis. This commentary identifies three key issues in evaluating evidence for a decline and in planning future, more co-ordinated efforts. These are (1) problems in combining data across different intelligence tests and/or different ages with potentially incompatible norms, task demands, and models of the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Interestingly, Hagerman et al have pointed out that abstract reasoning and symbolic language skills are often stressed in the IQ tests of later childhood and adolescence. That is, in some IQ tests, subtests are added to the assessment battery, thereby increasing the task demands at later ages (see also Hay 1994) and thus leading to apparent declines in IQ. To avoid this problem, we believe that investigators should endeavor to administer the same set of subtests to the same individuals at each time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Hagerman et al have pointed out that abstract reasoning and symbolic language skills are often stressed in the IQ tests of later childhood and adolescence. That is, in some IQ tests, subtests are added to the assessment battery, thereby increasing the task demands at later ages (see also Hay 1994) and thus leading to apparent declines in IQ. To avoid this problem, we believe that investigators should endeavor to administer the same set of subtests to the same individuals at each time point.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been argued that declining IQ in individuals with FXS might also be explained by inherent properties of cognitive tests, which for older children, may place greater emphasis on skills that are known to be specific weaknesses in this disorder (Hagerman et al 1989). As Hay (1994) has also pointed out, interpretation of standardized IQ data in individuals with FXS is extremely problematic because investigators have combined data from different tests, different sources and from different age-groups. This problem is compounded by the fact that most IQ tests have fewer items at the low ability levels, rendering the standardized IQ scores in individuals with FXS more imprecise and less reliable.…”
mentioning
confidence: 99%
“…However, Reiss and colleagues Freund, 1990, 1992] did not find an association between IQ and autistic behavior in males or in females [Mazzocco et al, 1997] with FXS. Some of the discrepancies noted in IQ scores may be related to the challenges of securing valid IQ scores in individuals with FXS [Dykens et al, 1989;Hay, 1994;Hooper et al, 2000;Skinner et al, 2004].…”
Section: Correlates Of Autistic Behavior In Fxsmentioning
confidence: 99%
“…The most prominent clinical feature of Fragile X however, is mild to severe mental retardation. Some studies in children and young adults have found progressive cognitive decline and increased autistic features with age, although some have argued that the finding may be related to the types of testing that were performed (Hagerman et al 1989; Hay 1994; Wright-Talamante et al 1996; Hatton et al 2006). In any case, extended longitudinal studies with adult patients have not been done, leaving a critical potential gap in our information regarding performance of Fragile X patients with aging.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, extended longitudinal studies with adult patients have not been done, leaving a critical potential gap in our information regarding performance of Fragile X patients with aging. Also, this issue has not been extensively examined in Fragile X animal models, where it can be studied quickly and cost effectively (Hagerman et al 1989; Hay 1994; Wright-Talamante et al, 1996; Jacquemont et al 2007). Furthermore, characterizing the effect that the loss of the protein product of FMR1 (FMRP) in aging may provide clues as to the pathophysiology of fragile X-associated tremor/ataxia syndrome (FXTAS), an age onset disease afflicting some FMR1 premutation carriers.…”
Section: Introductionmentioning
confidence: 99%